Reconstruction of the weight-bearing heel with nonsensate reverse sural artery flaps. Issue 7 (July 2021) - Park, Ji Hun; Choi, In Cheul; Hong, Tae Chang; Kang, Jong Woo; Park, Jong Woong
Highlights: Patients who underwent reverse sural artery flap for the reconstruction of the heel could expect to maintain the property for stable weight-bearing. The recovery of sensory function after reverse sural artery flap does not occur completely even in the long term. In this study, 86% of patients report that sensory deficit after reverse sural artery flap does not significantly impact their daily activity. Abstract: Background: The reverse sural artery flap (RSAF) is widely used to reconstruct foot and ankle defects. Although it is commonly used in a nonsensate type, there has been controversy as to whether it provides sufficient stability and durability when applied to weight-bearing heels. The aim of this study was to evaluate patient outcomes after weight-bearing heel coverage using a nonsensate RSAF. Methods: Twenty-three patients who underwent reconstruction surgery of the weight-bearing heel with RSAF from 2004 to 2018 in a tertiary hospital were retrospectively reviewed. All surgeries were performed without a sensate procedure. The patients' experience of pressure sore on the flap area and the ability to use normal footwear were investigated. Light touch, Semmes-Weinstein test (SWT), and two-point discrimination tests were assessed, along with postoperative wound complications. Results: Heel damage etiologies included malignant tumors in 14 (61%), trauma-related in 7 (30%) and diabetic ulcers in 2 (9%) patients. Patient mean age was 58 years (range, 18–93 years) and the mean follow-up period was 57 months (range, 12–185 months). The mean size of the flap was 64.1 cm2 (range, 20–169 cm 2 ). All flaps healed without major complications. All returned to daily living activities and 20 (86%) patients were able to use normal footwear. Of the 11 patients who had available measurement records, 8 (73%) showed a light touch sense. The mean SWT value was 4.31 (range, 3.61– 4.56). Two-point discrimination was not observed in any of the patients. Two patients had experienced superficial ulcers on the flap within a one-year postoperative period, which spontaneously healed and did not recur. No full-thickness ulcers were observed during the follow-up period. Conclusions: The results of this study suggest that patients who underwent nonsensate RSAF for the reconstruction of the heel could expect to maintain the property for stable weight-bearing without pressure sore.